Dampak Implementasi Kurikulum Merdeka terhadap Peningkatan Kualitas Pembelajaran Literasi & Numerasi di Kelas Awal Sekolah Dasar - florecyta; Dewi Rohmah; Agung Setyawan (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2025)
The implementation of the Independent Curriculum in elementary schools aims to improve the quality of learning, particularly in literacy and numeracy in early grades. This study demonstrates how curriculum policies that provide guidance to teachers influence students’ literacy and numeracy skills and the classroom learning process. The research methods used were literature review and qualitative analysis of reports of good practices and implementation challenges in several schools. Findings indicate that a project-based approach, differentiated learning, and an emphasis on meaningful learning can increase student engagement, creativity, and motivation, leading to improved literacy and numeracy skills. However, successful implementation is influenced by teacher readiness, principal support, and the availability of infrastructure. This study provides ongoing training for teachers, strengthened academic supervision, and the provision of relevant learning resources to ensure the goal of improving basic competencies is achieved.